Effectiveness of an Advanced Practice Nurse–Led Preoperative Telephone Assessment. Issue 2 (April 2016) - Ming Teh, Aline Hooi; Turner, Barbara S.; Tan, Siok Bee; Tham, Cheng Shi
Abstract : The purpose of this project was to determine the effectiveness of an advanced practice nurse–led preoperative telephone assessment in reducing day-of-surgery cancellations of patients at an ambulatory surgery center. We concluded that a good history obtained by a trained and experienced advanced practice nurse or registered nurse can reduce day-of-surgery cancellations. Patients who were identified at high risk for preoperative complications during the telephone assessment were referred to the preoperative evaluation clinic for further evaluation. Abstract : Supplemental Digital Content is Available in the Text.